The Effect of Work Stress on Work-Life Balance: The Mediation Role of the Organizational Work Environment - Firmawan, Mochamad (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study examines the influence of work stress on work-life balance, and the mediating role of the organizational work environment. The maritime industry, particularly the harbor master's office, is the focus of this research. Harbor masters often face high workloads, time pressures, and interactions with various stakeholders, which can lead to work stress and negatively impact their performance, well-being, and work-life balance. Additionally, the organizational work environment plays a crucial role in influencing the level of stress and work-life balance among employees. Factors such as office design, availability of facilities, organizational climate, and management support can contribute to work stress and employees' ability to manage work and personal demands. This study aims to investigate the relationship between work stress, work-life balance, and the mediating effect of the organizational work environment. The findings provide insights for organizations to develop effective strategies to manage employee stress and promote work-life balance, such as enhancing social support and implementing stress management programs. The study's results also highlight the importance of creating a conducive work environment that supports employee well-being and performance.